The pied Piper of Hamelin - Tamsin Hinrichsen (London Ladybird Books.Ltd, 2013)
The town of Hamelin is overrun with rats, and a mysterious piper offers to get rid of them in exchange for payment. He plays his magical pipe, leading the rats into the river to drown. When the townspeople refuse to pay him, the piper takes revenge by playing his pipe again$1 (Bthis time leading all the children away, never to return.s
The Pied Piper of Hamelin is a traditional German legend most famously retold in verse by Robert Browning. It tells the story of a mysterious piper who uses his magical music to rid the town of Hamelin of rats, but when the townspeople refuse to pay him, he takes his revenge by leading their children away. The tale explores themes of broken promises, consequences, and justice
Keywords: English,Fiction Book